Mariátegui, José Carlos. Mariátegui total. Edición Conmemorativa del Centenario de José Carlos Mariátegui, 2 Tomos, Lima, Empresa Editora Amauta,1994, 3905 p. - Beigel, Fernanda (1996)
Fil: Beigel, Fernanda. Universidad Nacional de Cuyo